2011
DOI: 10.5812/kowsar.1735143x.4216
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Drug Users Can Achieve a High Sustained Virological Response Rate: experience From Croatian Reference Center for Viral Hepatitis

Abstract: BackgroundHepatitis C virus (HCV) is one of the major infectious disease agents among injecting drug users (IVDUs). However, most of the IVDUs are not still treated.ObjectivesTo examine the treatment course, adherence, tolerability and safety profiles and SVR rates in IVDUs compared to non-IVDUs.Patients and MethodsDemographic and clinical data were collected from medical records of 345 adult patients diagnosed with chronic hepatitis C (CHC) who were treated with a PEG-IFN-α and ribavirin in Croatian Reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
6
1
2
Order By: Relevance
“…Our test group regarding the origin of infection was younger for 17.14 years with statistical significancy (p<0.001). Similar statistical significant difference was noted by the other authors in their studies (p=0.0001; p<0.001; p<0.001) (17, 18, 19). In other sudies the age of IVDU was 21-59 years and male was present by 65.9%-94% (20-25).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our test group regarding the origin of infection was younger for 17.14 years with statistical significancy (p<0.001). Similar statistical significant difference was noted by the other authors in their studies (p=0.0001; p<0.001; p<0.001) (17, 18, 19). In other sudies the age of IVDU was 21-59 years and male was present by 65.9%-94% (20-25).…”
Section: Discussionsupporting
confidence: 90%
“…EVR in our IVDU group was higher related to 84% in the same population that was noticed by Fried, but in the same time it was lower than excellent 100% among drug users in the study by Alvarez-Uria et all. ETR in the same population group was higher than ETR noticed in the studies of other authors (68%-90.1%) (20, 21, 26, 30) such as the SVR value in the literature (48.4% - 70.75%) (8, 17, 19, 20, 24, 25, 30-33). SVR among general population in the literature have had some higher value (51.04% - 66.7%) relating to our study (17, 23, 26, 29, 34).…”
Section: Discussioncontrasting
confidence: 58%
“…Genotype has implications for treatment; in most of these Asian countries, hepatitis C treatment is limited to urban centers or is not available, particularly for disenfranchised groups like injecting drug users. Combination therapy with HCV protease inhibitors and pegylated interferon has demonstrated sustained viral reduction in injecting drug users receiving treatment, particularly among those with type 3a [Robaeys et al, ; Hellard et al, ; Kurelac et al, ]. However, most treatment programs are limited to drug dependent individuals who have achieved abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Although their sample was much smaller (30 patients), the patients were selected for antiviral therapy according to the same principle, and they had very similar demographic and clinical characteristics and were treated by the same therapeutic protocol as ours. Only 30.46% of patients treated with standard viral therapy for CHC were opiate addicts who were included in the study of Kurelac et al from the Croatian Reference Center for Viral Hepatitis [34]. They reported that successful therapeutic response in their study was achieved in only 57.10% of all patients with CHC, and in 70.75% of intravenous drug addicts.…”
Section: Discussionmentioning
confidence: 99%